2019
DOI: 10.1097/md.0000000000013741
|View full text |Cite
|
Sign up to set email alerts
|

Simplified MIPI-B prognostic stratification method can predict the outcome well—retrospective analysis of clinical characteristics and management of newly-diagnosed mantle cell lymphoma patients from China

Abstract: Mantle cell lymphoma (MCL) is an invasive B-cell lymphoma with significant individual differences. Currently, MCL international prognostic index (MIPI) score and tumor cell proliferation index Ki-67 have been proved to be the most important prognostic factors. But the prognostic effect of these factors in Asian population is uncertain. This study aimed to analyze the disease characteristics and prognostic factors of Chinese MCL patients.A total of 83 cases of newly-diagnosed MCL patients diagnosed by the Depar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…12 In consistency with the former results in literature, when our patients were classified according to their MIPI scores, lowrisk patient group had a significantly longer median survival (p=0.04) than that of highrisk patients and also the patients at moderaterisk had significantly longer PFS (p=0.025) compared to high-risk patients. 13 Ki-67 proliferation index is identified as one of the factors with highest prognostic value 14 , however, only 10 patient in our cohort had documented Ki-67 proliferation index and therefore, we were not able to conduct survival analysis for Ki-67 proliferation index.…”
Section: Discussionmentioning
confidence: 85%
“…12 In consistency with the former results in literature, when our patients were classified according to their MIPI scores, lowrisk patient group had a significantly longer median survival (p=0.04) than that of highrisk patients and also the patients at moderaterisk had significantly longer PFS (p=0.025) compared to high-risk patients. 13 Ki-67 proliferation index is identified as one of the factors with highest prognostic value 14 , however, only 10 patient in our cohort had documented Ki-67 proliferation index and therefore, we were not able to conduct survival analysis for Ki-67 proliferation index.…”
Section: Discussionmentioning
confidence: 85%
“…analyzed 83 newly diagnosed MCL patients, and the results showed that B symptoms and the simplified MIPI were independent factors affecting OS and progression‐free survival in MCL patients. Based on the clinical data of this study, a prognostic model called s‐MIPI‐B was proposed 17 …”
Section: Discussionmentioning
confidence: 99%
“…Calibration curves for predicting MCL patients survival at 1-, 3-and 5-year for the IRPI (A1, A2, A3), MIPI (B1, B2, B3), and MIPI-c (C1, C2, C3) progression-free survival in MCL patients. Based on the clinical data of this study, a prognostic model called s-MIPI-B wasproposed 17. …”
mentioning
confidence: 99%
“…However, 10–20% of patients are characterized by a leukemic, non-nodal (LNN) presentation, with more indolent clinical behavior and prolonged survival [ 4 , 5 , 6 ]. The MCL international prognostic index (MIPI), together with Ki-67 expression via immunohistochemistry, represents the most used prognostic tool used at diagnosis [ 7 , 8 ]. Moreover, the absence of SOX-11 overexpression is associated with LNN presentation [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%